Improved Particle Swarm Optimization in Nutrition Adjustment for Hypertension Patient - Rosidha, Anisa Nur; Mardianto, Lutfi; Saputra, Ilham; Nasution, Achmad Suryadi (Syiah Kuala University, 2024)
Hypertension is one of the biggest contributors to the death cause in the world. This disease arises due to an unhealthy lifestyle and improper diet. In order to fulfill proper nutrition for people with hypertension, the composition of food for people with this disease needs to be regulated to produce optimal results according to their needs with the Improved Particle Swarm Optimization (IPSO) algorithm. Data collection was carried out on 96 patients with 1000 particles, a maximum iteration of 1000 and acceleration coefficients , , serta . The results show that the best fitness is 6,284 determined by price Rp 28.000 and 14 different variety of food. Based on the tests, the IPSO algorithm is effective in optimizing the nutrition of food composition with an accuracy rate of more than 99%.